1995
DOI: 10.1021/cm00059a013
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Intermolecular Interactions between Metallomesogens: Side-Chain Effects in Discotic Copper, Palladium, and Vanadyl Bis(.beta.-Diketonates)

Abstract: A systematic study of the liquid-crystalline properties of 30 metal bis (/3-diketonate) complexes (M = Cu, VO, Pd) that exhibit discotic mesophases is reported. This study has determined that the ability of the metal center to influence the mesophase stability depends upon the density of side chains. In the 10-side-chain complexes series 3, all of the materials were found to be liquid crystalline. In this series the M = VO analogues were found to have lower melting and clearing points than those with M = Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 1 publication
(2 reference statements)
7
54
0
4
Order By: Relevance
“…The resonance signals of the methylene protons of the major species isomers showed four peaks at 5.18 (dd, J = 23.8, 12.1 Hz, 2H, -CH 2 -), 4.78 (d, J = 11.9 Hz, 2H, -CH 2 -), 4.00 (t, J = 12.0 Hz, 2H, -CH 2 -), and 3.63 (d, J = 14.2 Hz, 2H, -CH 2 -). And the active methylene of -diketonates shows [20,[28][29][30]. It confirmed that oxygen atom of -diketonate did not bind to uranyl ion, also indicated by the FTIR spectra analysis.…”
Section: Proton Nmr Spectra Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…The resonance signals of the methylene protons of the major species isomers showed four peaks at 5.18 (dd, J = 23.8, 12.1 Hz, 2H, -CH 2 -), 4.78 (d, J = 11.9 Hz, 2H, -CH 2 -), 4.00 (t, J = 12.0 Hz, 2H, -CH 2 -), and 3.63 (d, J = 14.2 Hz, 2H, -CH 2 -). And the active methylene of -diketonates shows [20,[28][29][30]. It confirmed that oxygen atom of -diketonate did not bind to uranyl ion, also indicated by the FTIR spectra analysis.…”
Section: Proton Nmr Spectra Analysissupporting
confidence: 58%
“…[7,[20][21][22], which confirmed that oxygen atoms of carbonyl group of -diketonate did not bind to uranyl ion. The bands at 1640-1643 cm…”
Section: Ftir Spectra Analysismentioning
confidence: 66%
“…Im Fall dendritischer Texturen entstehen häufig "Blumen"-Muster. [25] Darüber hinaus sind die relativ seltenen Sphärulit-(Abbildung 8 c) und Fingerprint-Texturen [26] bekannt. Diese Fingerprint-Texturen weisen keine Analogie zu denen cholesterischer Mesophasen auf, wo die äquidistanten Streifen die Periodizität der durch Chiralität induzierten helicalen Struktur widerspiegeln.…”
Section: Strukturen Von Flüssigkristallinen Phasenunclassified
“…There have been a very few example exhibiting more than three Col h mesophases in one compound. However, Swager and his co-workers also reported that the long chain-substituted b-diketonato copper(II) complexes exhibited four different Col hd mesophases [24]. We reported another example of the phthalocyanine-based liquid crystals showing plural Col h mesophases in one compound [25].…”
Section: Spontaneous Perfect Homeotropic Alignmentmentioning
confidence: 66%